Cherokee and Dakota language letters: Illustrations of nineteenth century discourse. - Anderson, Laura Lee. (My University, 1999)
This dissertation concerns nineteenth century Cherokee and Dakota discourse, exemplified by the individual writers of native language letters. The first chapter outlines the goals, the data, and the methods of this dissertation. Chapter two historically compares the nineteenth century Cherokee and Dakota literacy experience with the American's experience. Chapter three compares the norms of communication in letter form, the structuring, rhetorical presentation, the agency, and interaction in each language as manifest by native writers. Chapter four draws conclusions about the compared historical experience, adds a sociocultural description of nineteenth century Cherokee and a Dakota letter writing, and begins a description of Cherokee and Dakota discourse found in nineteenth century letters. Appendix I compares the orthographies as they pertain to language specific attributes influencing translation and the recoverability of language specific information.
Keywords: Language, General.; Dakota language.; Cherokee language.; Anthropology, Cultural.